Electrophysiological neuroimaging of the central effects of S-adenosyl-l-methionine by mapping of electroencephalograms and event-related potentials and low-resolution brain electromagnetic tomography - Saletu, Bernd; Anderer, Peter; Di Padova, Carlo; Assandri, Alessandro; Saletu-Zyhlarz, Gerda Maria (The American journal of clinical nutrition, 2002)
Background: S-Adenosyl-l-methionine (SAMe, or ademetionine) is a naturally occurring molecule used as both a nutraceutical and a pharmaceutical to treat depression. Objective: The central mode of action of SAMe was investigated in 20 healthy volunteers by mapping of electroencephalograms (EEGs) and event-related potentials (ERPs) and low-resolution brain electromagnetic tomography (LORETA). Design: In an acute and subacute, double-blind, placebo-controlled, crossover study, subjects received in random order infusions of 800 mg SAMe and placebo for 7 d, with a washout period of 3 wk between the 2 treatment periods. EEG recordings were made 0, 1, 3, and 6 h after and ERP recordings were made 0 and 1 h after the drug infusions on days 1 and 7. Results: Multivariate analyses of variance and Hotelling T2 tests showed significant acute and subacute encephalotropic effects of SAMe compared with placebo. Acute pharmaco-EEG changes were typical of classic antidepressants of the thymoleptic type; subacute alterations were typical of cognition enhancers. Regarding ERPs, standard N1 and P2 latencies were shortened, and target P300 latencies were lengthened. N1 amplitudes increased after subacute treatment, and temporooccipital P300 amplitudes increased after the acute dose. Similar changes were described for antidepressants. LORETA showed that the N2 source strength increased in both the left and the right temporal lobes, whereas the P300 source strength increased in the dorsolateral prefrontal regions and decreased in the ventral limbic regions. Conclusion: EEG-ERP mapping identified SAMe as an antidepressant. LORETA targeted brain regions crucial in the therapeutic efficacy of antidepressants.